THE TRANSLATOR BOOK PROJECT - Rachad Salhi (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
This article discusses the rapid shift toward digitization in the context of globalization and software development, and the resulting widespread adoption of the e-book along with the evolving needs of learners in the modern era. The article begins with the idea of developing the digital translating book as an innovative educational tool for teaching Arabic to non-native speakers, by integrating the parallel-translation (Bilanguage) system with interactive features based on virtual reality, augmented reality, and artificial intelligence technologies. It reviews the concept of parallel translation and its applications, the method of displaying the original text alongside its translation, and its role in enhancing comprehension, developing reading and translation skills, and facilitating access to meanings through directly clicking on words to obtain audio and visual definitions.